2005
DOI: 10.1152/japplphysiol.00360.2004
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training increases total daily energy expenditure in disabled older women with coronary heart disease

Abstract: Physical activity energy expenditure (PAEE) is a determinant of prognosis and fitness in older patients with coronary heart disease (CHD). PAEE and total energy expenditure (TEE) are closely related to fatness, physical function, and metabolic risk in older individuals. The goal of this study was to assess effects of resistance training on PAEE, TEE, and fitness in older women with chronic CHD and physical activity limitations (N = 51, mean age: 72 + 5 yr). The study intervention consisted of a progressive, 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 45 publications
2
88
0
13
Order By: Relevance
“…In addition to mortality benefits described in both meta-analyses and single-center studies, 20 -24 the most predictable benefit of CR is an increase in exercise tolerance, 16 along with benefits related to physical functioning. 25 Selective use of resistance training also has been shown effective in reducing measures of disability in this patient population 26,27 and may be associated with increases in peak V O 2 , although this is controversial. 28 Finally, it should be noted that the magnitude of training-induced increases in peak V O 2 has been shown to independently predict a decrease in cardiovascular mortality.…”
mentioning
confidence: 99%
“…In addition to mortality benefits described in both meta-analyses and single-center studies, 20 -24 the most predictable benefit of CR is an increase in exercise tolerance, 16 along with benefits related to physical functioning. 25 Selective use of resistance training also has been shown effective in reducing measures of disability in this patient population 26,27 and may be associated with increases in peak V O 2 , although this is controversial. 28 Finally, it should be noted that the magnitude of training-induced increases in peak V O 2 has been shown to independently predict a decrease in cardiovascular mortality.…”
mentioning
confidence: 99%
“…Similar to aerobic exercise, resistance training has been reported to enhance insulin sensitivity (23)(24)(25), daily energy expenditure (26,27), and quality of life (20,28). Furthermore, resistance training has the potential for increasing muscle strength (13,29,30), lean muscle mass (31), and bone mineral density (32,33), which could enhance functional status and glycemic control and assist in the prevention of sarcopenia and osteoporosis.…”
mentioning
confidence: 99%
“…Many studies have shown that a cardiac rehabilitation program consisting of aerobic and resistance training is an effective intervention to restore physical function 10,11) and exercise capacity, 12,13) and to reduce difficulty in physical activities of daily living 14,15) in cardiac patients. Several meta-analyses of randomized trials 12,16) have also confirmed that a cardiac rehabilitation program consisting of lifestyle modification and prolonged exercise training in the recovery phase (after hospital discharge) is more effective in reducing morbidity and mortality in cardiac patients.…”
Section: Discussionmentioning
confidence: 99%